แอปพลิเคชันช่วยในการตรวจสอบคุณภาพสำหรับกระบวนการก่อสร้าง (ระบบส่วนหลังบ้าน) - คุปติพงศ์ สุวรรณไตรย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
We intend to develop the application in React Native framework that helps with the validation process during construction in order to enhance the communication efficiency within the organization. Backend development team chooses AWS (Amazon Web Services) to deploy our backend system. We pick AWS Lambda, Amazon API Gateway, Amazon S3, Amazon CloudWatch, AWS Amplify, Amazon SNS, Amazon Cognito, AWS IAM and the last one is Amazon DynamoDB. Not only Amazon services, we also include Expo Server and Firebase Cloud Messaging to take care of push notifications. Our application has been tested by real users of reliable construction companies in field of performance and functional. The result is satisfactory. In backend, target users are frontend developers so we invite them to test our backend system, favorable outcome returned.